Measurement of trilinear gauge boson couplings from WW+WZ→lνjj events in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
We present a direct measurement of trilinear gauge boson couplings at γWW and ZWW vertices in WW and WZ events produced in pp̄ collisions at s=1.96TeV. We consider events with one electron or muon, missing transverse energy, and at least two jets. The data were collected using the D0 detector and correspond to 1.1fb-1 of integrated luminosity. Considering two different relations between the couplings at the γWW and ZWW vertices, we measure these couplings at 68% C.L. to be κγ=1.07-0.29+0.26, λ=0.00-0.06+0.06, and g1Z=1.04-0.09+0.09 in a scenario respecting SU(2)L U(1)Y gauge symmetry and κ=1.04-0.11+0.11 and λ=0.00-0.06+0.06 in an equal couplings scenario. © 2009 The American Physical Society.